1999
DOI: 10.1103/physreva.60.4114
|View full text |Cite
|
Sign up to set email alerts
|

Bogoliubov dispersion relation and the possibility of superfluidity for weakly interacting photons in a two-dimensional photon fluid

Abstract: The Bogoliubov dispersion relation for the elementary excitations of the weakly-interacting Bose gas is shown to hold for the case of the weakly-interacting photon gas (the "photon fluid") in a nonlinear Fabry-Perot cavity. The chemical potential of a photon in the 2D photon fluid does not vanish. The Bogoliubov relation, which is also derived by means of a linearized fluctuation analysis in classical nonlinear optics, implies the possibility of a new, superfluid state of light. The theory underlying an experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
141
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(142 citation statements)
references
References 12 publications
1
141
0
Order By: Relevance
“…As an example, consider a 0.1-m-long cavity with T = 2 10 −2 filled with 85 Rb vapor at 80 0 C corresponding to 10 12 atoms/cm 3 . The self-defocusing regime is obtained by detuning the laser to the red side of the hyperfine transition 5S 1/2 (F = 2) − 5P 3/2 (F = 3) (λ ∼ 780 nm) [13,14]. The detuning must be chosen in order to have the strongest nonlinearity compatible with an absorption lower than T. A refractive index change ∆n = n 2 ρ 0 = 10 −6 leads to a sound speed c s = 3 10 5 m/s.…”
Section: Experimental Proposalmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, consider a 0.1-m-long cavity with T = 2 10 −2 filled with 85 Rb vapor at 80 0 C corresponding to 10 12 atoms/cm 3 . The self-defocusing regime is obtained by detuning the laser to the red side of the hyperfine transition 5S 1/2 (F = 2) − 5P 3/2 (F = 3) (λ ∼ 780 nm) [13,14]. The detuning must be chosen in order to have the strongest nonlinearity compatible with an absorption lower than T. A refractive index change ∆n = n 2 ρ 0 = 10 −6 leads to a sound speed c s = 3 10 5 m/s.…”
Section: Experimental Proposalmentioning
confidence: 99%
“…As a consequence light propagating in a self-defocusing medium induces a local negative bending of the refractive index which, in turn, affects the light beam itself. At a microscopic level this can be described in terms of an atom-mediated repulsive interaction between photons which leads to the formation of a "photon-fluid" [12,13]. It will be shown that linear excitations of such fluid (sound waves) propagate in an effective curved spacetime determined by the physical properties of the optical flow.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with a suitable generalization of the formalism presented above, we could be able to develop a theoretical description of the dynamical aspects of a recently proposed experiment [16] (currently in progress), regarding the BoseEinstein condensation in a weakly-interacting photon gas in a nonlinear Fabry-Perot cavity [17]. Here, τ ≡ (h/ma 2 )t is a dimensionless time and ρ0 ≡ a 3 |ϕ0| 2 is a dimensionless density.…”
mentioning
confidence: 99%
“…Similar equations were first derived for multimode lasers, then applied to light in microcavities [54]. Its solu-tions are Bogoliubov modes of sound [55,56] or collective breathing [57] or scissors [58] modes.…”
Section: Mean-field Modelsmentioning
confidence: 90%